Unpacking students' epistemic cognition in a physics problem‐solving environment. Issue 5 (8th November 2019) - Lindfors, Maria; Bodin, Madelen; Simon, Shirley
Abstract: It is a widely held view that students' epistemic beliefs influence the way they think and learn in a given context, however, in the science learning context, the relationship between sophisticated epistemic beliefs and success in scientific practice is sometimes ambiguous. Taking this inconsistency as a point of departure, we examined the relationship between students' scientific epistemic beliefs (SEB), their epistemic practices, and their epistemic cognition in a computer simulation in classical mechanics. Tenth grade students' manipulations of the simulation, spoken comments, and behavior were screen and video‐recorded and subsequently transcribed and coded. In addition, a stimulated recall interview was undertaken to access students' thinking and reflections on their practice, in order to understand their practice and make inferences about their process of epistemic cognition. The paper reports on the detailed analysis of the data sets for three students of widely different SEB and performance levels. Comparing the SEB, problem solutions and epistemic practices of the three students has enabled us to examine the interplay between SEB, problem‐solving strategies (PS), conceptual understanding (CU), and metacognitive reflection (MCR), to see how these operate together to facilitate problem solutions. From the analysis, we can better understand how different students' epistemic cognition is adaptive to the context. The findings have implications for teaching science and further research into epistemic cognition.